Numerical analysis and thermal fatigue life prediction of solder layer in a SiC-IGBT power module - Dianhao Zhang; Xiao-guang Huang; Bin-liang Cheng; Neng Zhang (Fracture and Structural Integrity)
Limited by the mechanical properties of materials, silicon (Si) carbide insulated gate bipolar transistor (IGBT) can no longer meet the requirements of high power and high frequency electronic devices. Silicon carbide (SiC) IGBT, represented by SiC MOSFET, combines the excellent performance of SiC materials and IGBT devices, and becomes an ideal device for high-frequency and high-temperature electronic devices. Even so, the thermal fatigue failure of SiC IGBT, which directly determines its application and promotion, is a problem worthy of attention. In this study, the thermal fatigue behavior of SiC-IGBT under cyclic temperature cycles was investigated by finite element method. The finite element thermomechanical model was established, and stress-strain distribution and creep characteristics of the SnAgCu solder layer were obtained. The thermal fatigue life of the solder was predicted by the creep, shear strain and energy model respectively, and the failure position and factor of failure were discussed.